Managing Costs for Efficiency in Production - Agung Listiadi (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: This study aims to provide cost information for the benefit of costs as a measure of the efficiency of a business. Planning tool, meaning that business planning is definitely related to income and costs. Cost control, meaning comparing the costs that should have been incurred to produce one unit of product with the actual costs incurred. Cost is an important factor in ensuring a company's victory in competition in the market. Consumers will choose producers who are able to produce high quality products and services at low prices. Contemporary Cost Management Systems emphasize tracking over allocation. And activity-based management is at the heart of contemporary operations control systems. Design/methodology/approach: This study used a descriptive research method. Data is the document obtained financial statement for the period of 2022. As for the subjects in this study are companies engaged in manufacturing, by calculating the cost based on the financial statements in 2022. Findings: Based on the results of research, it can be concluded that recording costs in the company's internal or known as cost accounting is useful to assist company management in preparing plans or making decisions related to finance. There are at least two main factors that must be considered in choosing a cost driver, namely: measurement costs and the degree of correlation between the cost driver and actual overhead consumption. Cost drivers are divided into two categories, namely structural cost drivers and executional cost drivers. The cost driver is the basis used to charge the costs accumulated in the cost pool to products. So that by calculating costs through a Time Driven activity-based costing system, companies obtain more precise and accurate information. Research limitations/implications: The limitation in this study is that calculating cost can only be done for one entity. Practical implications: The results of this study can be used as a comparison in this cost has a function to measure production costs with the cost of production results. Activity based accounting will make it easier for accountants to understand the costs and benefits derived from the products the company produces. Originality/value: The focus of the research is to find ways to calculate the effectiveness of human resources, means of production, as well as the raw materials for the products to be used. This type of cost accounting also calculates the average direct cost required by the company during its production process. Paper type: Research paper.